Effect of graft sizing in valve-sparing aortic root replacement for bicuspid aortic valve: The Goldilocks ratioCentral MessagePerspective - Perry S. Choi, MD; Amit Sharir, BA; Yoshikazu Ono, MD; Masafumi Shibata, MD; Alexander D. Kaiser, PhD; Yuanjia Zhu, MD, PhD; Alison L. Marsden, PhD; Y. Joseph Woo, MD; Michael R. Ma, MD; Joon Bum Kim, MD, PhD (JTCVS Techniques)
Objective: To investigate the effect of graft sizing on valve performance in valve-sparing aortic root replacement for bicuspid aortic valve. Methods: In addition to a diseased control model, 3 representative groups—free-edge length to aortic/graft diameter (FELAD) ratio <1.3, 1.5 to 1.64, and >1.7—were replicated in explanted porcine aortic roots (n = 3) using straight grafts sized respective to the native free-edge length. They were run on a validated ex vivo univentricular system under physiological parameters for 20 cycles. All groups were tested within the same aortic root to minimize inter-root differences. Outcomes included transvalvular gradient, regurgitation fraction, and orifice area. Linear mixed effects model and pairwise comparisons were employed to compare outcomes across groups. Results: The diseased control had mean transvalvular gradient 10.9 ± 6.30 mm Hg, regurgitation fraction 32.5 ± 4.91%, and orifice area 1.52 ± 0.12 cm2. In ex vivo analysis, all repair groups had improved regurgitation compared with control (P < .001). FELAD <1.3 had the greatest amount of regurgitation among the repair groups (P < .001) and 1.5-1.64 the least (P < .001). FELAD <1.3 and >1.7 exhibited greater mean gradient compared with both control and 1.5 to 1.64 (P < .001). Among the repair groups, 1.5 to 1.64 had the largest orifice area, and >1.7 the smallest (P < .001). Conclusions: For a symmetric bicuspid aortic valve, performance after valve-sparing aortic root replacement shows a bimodal distribution across graft size. As the FELAD ratio departs from 1.5 to 1.64 in either direction, significant increases in transvalvular gradient are observed. FELAD <1.3 may also result in suboptimal improvement of baseline regurgitation.